2005
DOI: 10.1152/ajpheart.00969.2004
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in the development of angiotensin II-induced hypertension in conscious mice

Abstract: Sex has an important influence on blood pressure (BP) regulation. There is increasing evidence that sex hormones interfere with the renin-angiotensin system. Thus the purpose of this study was to determine whether there are sex differences in the development of ANG II-induced hypertension in conscious male and female mice. We used telemetry implants to measure aortic BP and heart rate (HR) in conscious, freely moving animals. ANG II (800 ng.kg(-1).min(-1)) was delivered via an osmotic pump implanted subcutaneo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

33
193
2
3

Year Published

2006
2006
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 222 publications
(231 citation statements)
references
References 71 publications
33
193
2
3
Order By: Relevance
“…Our blood pressure results are limited because we only used a noninvasive tail-cuff method, a technique that has received criticism in the past. Although we may have missed subtle blood pressure differences between genotypes with this technique, the overall effect of ANG II treatment on blood pressure was clearly evident and within the range reported by others investigators with similar doses in which either the tail-cuff method or telemetric devices were being used (13,41).…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Our blood pressure results are limited because we only used a noninvasive tail-cuff method, a technique that has received criticism in the past. Although we may have missed subtle blood pressure differences between genotypes with this technique, the overall effect of ANG II treatment on blood pressure was clearly evident and within the range reported by others investigators with similar doses in which either the tail-cuff method or telemetric devices were being used (13,41).…”
Section: Discussionsupporting
confidence: 77%
“…The dose of 1.0 g ⅐ kg Ϫ1 ⅐ min Ϫ1 ANG II is most commonly used in rodents and causes relevant elevations of blood pressure as measured by tail-cuff plethysmography or telemetric devices (13,41).…”
Section: Ang II Infusionmentioning
confidence: 99%
“…It has been reported that chronic low-dose ANG II-induced hypertension, which develops over a period of days, is not due to the peripheral vasoconstrictor activity of ANG II, but is most likely the result of excitation of the sympathetic nerve activity (8,17). Recent studies from our laboratory have shown in mice that decreases in blood pressure induced by ganglionic blockade are much smaller on day 1 as compared to day 7 of ANG II infusion, thus suggesting that an enhancement of sympathetic outflow contributes to the ANG II-induced progressive increase in blood pressure (21). The results obtained by Hendel and Collister (18) confirm that the chronic phase of ANG II hypertension has a significant neurogenic component and that this sympathoexcitation is mediated via the subfornical organ.…”
Section: Sex Differences In Angiotensin Iiinduced Hypertensionmentioning
confidence: 90%
“…Implantable mouse BP transmitters (TA11PA-C20; Data Sciences International, St Paul, MN, USA) were used to directly measure arterial pressure in individual conscious and freely moving mice [28,29]. The mice were anaesthetised and the left carotid artery was isolated.…”
Section: Methodsmentioning
confidence: 99%